Mucolytic treatment of chronic rhinosinusitis in a murine model of primary ciliary dyskinesia - Yin, Weining; Golliher, Hannah L.; Ferguson, Amy J.; Kimbell, Julia S.; Livraghi-Butrico, Alessandra; Rogers, Troy D.; Grubb, Barbara R.; Kimple, Adam J.; Ostrowski, Lawrence E. (Frontiers in Molecular Biosciences, 2023)
Background – Genetic defects in motile cilia cause primary ciliary dyskinesia (PCD), a rare disease with no specific therapeutics. Individuals with PCD often have impaired fertility and laterality defects, and universally suffer from upper and lower airway disease. Chronic rhinosinusitis is a universal feature of PCD, and mucus accumulation and subsequent infections of the sinonasal cavity cause significant morbidity in individuals with PCD. Despite this, there are no approved treatments that specifically target mucus. Objective – The goals of this study were to determine if computed tomography (CT) imaging could be used to quantify mucus accumulation and if the use of a mucolytic agent to reduce disulfide cross-links present in mucins would improve the effectiveness of nasal lavage at removing mucus in a murine model of PCD. Methods – Adult mice with deletion of the axonemal dynein Dnaic1 were imaged using CT scan to characterize mucus accumulation. Animals were then treated by nasal lavage with saline, with/without the disulfide reducing agent tris(2-carboxyethyl)phosphine. Post treatment CT scans were used to quantify improvement in the sinonasal cavity. Results – Mucus accumulation in the nasal cavity was readily quantified by CT. Compared to sham treated control animals, nasal lavage with/without mucolytic resulted in a significant reduction of accumulated mucus (p<0.01). Treatment with the mucolytic showed a greater reduction of accumulated mucus compared to treatment with saline alone. Conclusion – The results suggest that inclusion of a mucolytic agent may increase the effectiveness of nasal lavage at reducing mucus burden in PCD.